Macroprudential regulation in a GSGE model of the Philippines with financial-real linkages - Pagaduan, Jesson A. (Animo Repository, 2016)
We develop a small open economy New Keynesian DSGE model of financial-real linkages with banking intermediation and macroprudential regulation. The study has two main objectives: (i) understand the role of banking intermediation and financial frictions in the transmission of monetary policy; and (ii) examine the implications of macroprudential regulation of the banking system to the real economy. The results of our research suggest that although the macroprudential tools used by central banks may achieve the goal of safeguarding financial stability of the banking system, it is important to watch out for their effects to the short-run business cycle fluctuations of the real economy. © 2016 by De La Salle University.